Reduction in corpora lutea number in obese melanocortin-4-receptor-deficient mice - Schöneberg Torsten; Merkwitz Claudia; Schulz Angela; Sandrock Mara; Spanel-Borowski Katharina; Ricken Albert (BMC, 2009)
Abstract Obese melanocortin-4-receptor-deficient (MC4R-/-) male mice are reported to have erectile dysfunction, while homozygous MC4R-/- female mice are apparently fertile. A recently established obese mouse strain, carrying an inactivating mutation in the MC4R gene, revealed difficulties in breeding for the homozygous female mice. This prompted us to determine the presence of follicles and corpora lutea (CL) in ovaries of MC4R-/- mice aged 3-6 months in comparison to wild type (MC4R+/+) littermates. Serial sections of formaldehyde-fixed ovaries of mice with vaginal signs of estrus and metestrus were assessed for the number of healthy and regressing follicles and CL. The number of CL, as an estimate for the ovulation rate, decreased to zero during aging in MC4R-/- mice. The number of small- (diameter 100-200 micrometer) and large-sized follicles namely antral follicles (diameter >200 micrometer) were slightly increased in MC4R-/- compared to MC4R+/+ mice. Greater differences were found in very large to cystic follicles, which were more numerous in MC4R-/- mice. The number of regressing antral follicles was higher in the MC4R-/- group compared to the MC4R+/+ group. This was associated with a wide range in the number of collapsed zonae pellucidae as the last remnants of regressed follicles. A conspicuous hypertrophy of the interstitial cells was noted in 6-month-old MC4R-/- mice. In conclusion, cystic follicles and the reduction in CL number point to a decreased ovulation rate in obese MC4R-/- mice.